The Influence of Content Marketing on Customer Advocacy with Entertainment Intention as an Intervening Variable on Tiktok - Uswatun Khasanah; Nurafni Rubiyanti; Arry Widodo; Anita Silvianita (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the relationship between marketing content and customer advocacy mediated by entertainment intentions using the idea of the stimulus - organism - response (SOR) framework on TikTok social media. The research model used is Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. The results showed that content marketing is the main key to increasing customer engagement. This engagement can trigger customer advocacy, where customers actively promote brands based on the positive experiences they feel. The role of entertainment intentions in content marketing is also important to provide consumer self-awareness and identity formation so that it will affect customer advocacy.